PENGARUH TEKNIK RELAKSASI GENGGAM JARI TERHADAP INTENSITAS NYERI PASIEN POST OPERASI SECTIO CAESAREA - Mariene Dolang (Pasapua Health Journal, 2019)
Surgery through the section caesarea will cause pain for the mother who lives it. Non-pharmacological management of hand-held relaxation techniques can be used to reduce pain intensity scale. The purpose of this study was to see the effect of giving hand held relaxation techniques to pain intensity in patients with postoperative section caesarea. The research design used was Pre Experiment with the approach of The One Group Pratest Posttest. The population in this study were all postoperative patients in the section caesarea at the Nifas Room of the RSUD Dr. M. Haulussy Ambon. Sampling using purposive sampling technique with a total sample of 20 respondents. The results of the study obtained from 20 samples there were 85% of respondents who experienced severe pain before hand held finger relaxation and after hand held finger relaxation there were no respondents who experienced severe pain. From the results of the analysis it is known that there is an effect of giving finger hand relaxation techniques to pain intensity in patients with postoperative section caesarea (0,000). It is recommended to postpartum mothers to perform finger handheld relaxation techniques to reduce pain post operation section caesarea.